Investing in pre-emerging markets : opportunities for investment of risk capital in the LDCs (UN GenevaCH, 1998)
Focuses on the identification of investment opportunities in the LDCs of interest to foreign private investors, with special reference to the sectors of tourism, agro-related industries and infrastructure.
DC